Preparation and characterization of CrNxOy thin films: The effect of composition and structural features on the electrical behavior - Arvinte, R. (2011)
Metallic oxynitrides have attracted the attention of several researchers in the last decade due to their versatile properties. Through the addition of a small amount of oxygen into a transition metal nitride film, the material’s bonding states between ionic and covalent types can be tailored, thus opening a wide range of electrical, optical, mechanical and tribological responses. Among the oxynitrides, chromium oxynitride (CrN x O y ) has many interesting applications in different technological fields. In the present work the electrical behavior of CrN x O y thin films, deposited by DC reactive magnetron sputtering, were investigated and correlated with their compositional and structural properties. The reactive gas flow, gas pressure, and target potential were monitored during the deposition in order to control the chemical composition, which depend strongly on reactive sputtering process. Depending on the particular deposition parameters that were selected, it was possible to identify three types of films with different growth conditions and physical properties. The electrical resistivity of the films, measured at room temperature, was found to depend strongly on the chemical composition of the samples.